5‐Year outcomes of the prospective and randomized CISTCERT study comparing steroid withdrawal to replacement of cyclosporine with everolimus in de novo kidney transplant patients. (31st December 2020) - Pipeleers, Lissa; Abramowicz, Daniel; Broeders, Nilufer; Lemoine, Alain; Peeters, Patrick; Van Laecke, Steven; Weekers, Laurent E.; Sennesael, Jacques; Wissing, Karl M.; Geers, Caroline; Bosmans, Jean‐Louis
Summary: Withdrawal of either steroids or calcineurin inhibitors are two strategies to reduce treatment‐related side effects and improve long‐term outcomes of kidney transplantation. The CISTCERT study compared the efficacy and safety of these two strategies. In this multicenter, randomized controlled trial, 151 incident kidney transplant recipients received cyclosporine (CsA), mycophenolic acid (MPA), and steroids during three months, followed by either steroid withdrawal (CsA/MPA) or replacement of cyclosporine with everolimus (EVL) (EVL/MPA/steroids). 5‐year patient survival (89% vs. 86%; P  = NS) and death‐censored graft survival (95% vs. 96%; P  = NS) were comparable in the CsA/MPA and EVL/MPA/steroids arm, respectively. 51 CrEDTA clearance was comparable in the intention‐to‐treat analysis, but in the on‐treatment population, the EVL/MPA/steroids arm exhibited a superior 51 CrEDTA clearance at 1 and 5 years after transplantation (61.6 vs. 52.4, P  = 0.05 and 59.1 vs. 46.2ml/min/1.73 m 2, P  = 0.042). Numerically more and more severe rejections were observed in the EVL/MPA/steroids arm, which also experienced a higher incidence of posttransplant diabetes (26% vs. 6%, P  = 0.0016) and infections. No significant differences were observed in cardiovascular outcomes and malignancy. Both regimens provide an excellent long‐term patient survival and graft survival. Regarding graft function, EVL/MPA/steroids is an attractive strategy for patients with good tolerability who remain free of rejection. (ClinicalTrials.gov number: NCT00903188; EudraCT Number 2007‐005844‐26).